DETERMINANTS OF FIRM VALUE: THE ROLES OF CSR DISCLOSURE, PROFITABILITY, SIZE, AND LEVERAGE - Kelvin, Kelvin; Susanti, Merry; Verawati , Verawati (International Journal of Application on Economics and Business, 2025)
Firm value is a ratio used to describe the value owned by a company. This ratio provides information related to management's effectiveness in managing the company. Firm value is one of the key pieces of information that influences managers and investors in making economic decisions. This study aimed to provide empirical proof concerning the influence of CSR disclosure, profitability, size, and leverage towards firm value. This study focuses on energy and consumer non-cyclical companies that are listed in IDX. A purposive sampling method was employed to retrieve the sample. 32 companies were selected over three consecutive years, from 2021 to 2023, resulting in a total of 96 data. Eviews 12 software program was utilized to process the data. The research utilized a multiple linear regression model for hypothesis testing. The appropriate estimation model for multiple linear regression was the Random Effect Model (REM). Findings indicated that CSR disclosure, size, and leverage did not significantly affect on firm value, whereas profitability exerted a substantial positive influence on firm value. This study expanded the understanding of factors that influence company value and helped managers take concrete steps to enhance firm value, such as focusing efforts on improving profitability. Additionally, it assisted investors in analyzing factors that affect company value, especially the company's profitability potential, to make informed investment decisions.